New bounds on the connected-pseudoachromatic index of complete graphs - Jorge Cervantes-Ojeda; María C. Gómez-Fuentes; Christian Rubio-Montiel (Electronic Journal of Graph Theory and Applications (EJGTA), 2026)
We improve several previously known bounds of the connected-pseudoachromatic index of complete graphs. We apply a Rank Genetic Algorithm to find experimental solutions above the known lower bounds and then we obtain an approximation of the upper bound to verify and compare to the empirically obtained results.